Effect Of Intellectual Capital On The Performance Indicators Of Indian Metal Firms Listed In National Stock Exchange Of India Limited - Vadivel Thanikachalam, Murugesan Selvam, Mariappan Raja, Palanisamy Bhuvaneswari, Dhamotharan Dhanasekar (International Journal of Advanced Science and Technology, 2020)
This study examined the effect of intellectual capital imbedded in the metal companies in India. This paper used the secondary data gathered from Prowess database, between 2010 and 2019. Intellectual capital is measured by using Pulic’s Value Added Intellectual Coefficient (VAIC) and its components. This paper found that there was positive correlation between IC and performance indicators of metal companies, particularly with ROA and ROE, except ATO while HCE, SCE, CEE and VAIC impacted the performance indicators positively. Future attempt could be made towards other manufacturing industries, by using this model.